Human resilience and cultural change in the construction industry: communication and relationships in a time of enforced adaptation - Aasen, Audun Flaget; Klakegg, Ole Jonny (Frontiers in Built Environment, 2023)
The construction industry will need to change to enhance performance and deliver more with less. This paper investigates how social science perspectives may help addressing challenges associated with enforced transformation. We turned to a leading construction company in Norway to study the role of human resilience and cultural understanding in the construction industry's ability to adapt to new technologies and practices. Results from a comprehensive survey with 541 respondents are analyzed and discussed against three concepts from literature: culture, resilience, and psychological safety. The results show that the consequences of enforced changes are perceived differently by different groups in the organization. Management teams found stronger impact of Covid-19, and they are more likely to carry forward changes into the future. We found confirmation that older employees and those with long experience found the effect to be stronger and more detrimental than younger. We also found that experienced individuals perceived communication and collaboration to worsen over the enforced change. However, the organizational culture represents a stabilizing force and individuals demonstrated resilience facing uncertainty. Team role affiliations also influence how people perceive the consequences. Therefore, organizations should carefully consider team dynamics and individual experience levels in their change management strategies. New technologies can enhance collaboration and communication if the organization also strengthen psychological safety, trust, and involvement. The resulting effect might be the best path for project-based organizations to adapt and reshape for the digital era.